Sharing communication insights of the citizen science program Plastic Pirates—best practices from 7 years of engaging schoolchildren and teachers in plastic pollution research - Dittmann, Sinja; Kiessling, Tim; Mederake, Linda; Hinzmann, Mandy; Knoblauch, Doris; Böhm-Beck, Marianne; Knickmeier, Katrin; Thiel, Martin (Frontiers in Environmental Science, 2023)
Engaging the general public in research processes through citizen science allows for innovative scientific studies and makes science accessible to the general public. Effective communication strategies are crucial for the success of such initiatives. The citizen science program Plastic Pirates investigated the plastic pollution of rivers and implemented a variety of communication strategies with participating schoolchildren, teachers, and youth groups (e.g., sport associations, scouts or educational vacation programs, representing approximately 6% of participating groups). These were continuously revised and adapted since its start in 2016. Without time-efficient communication and strategies to keep track of conversations, it would not have been possible to achieve the scientific and educational goals of the program, i.e., to help teachers increase the environmental awareness and scientific literacy of their schoolchildren, and to produce peer-reviewed articles based on the collected citizen science data. Communication within the Plastic Pirates program was divided into four distinct phases: 1) recruiting and motivating participants, 2) coordination and guidance of participants, 3) data reception and revision, and 4) sharing updates and results. Some of the obstacles that had to be overcome to achieve successful communication were e.g., time constraints to obtaining scientific data from the participants, the time lag between the active involvement of the participants and the actual data analysis and publication of results, and limited personnel resources available for communication efforts. Our recommendations for other citizen science practitioners include regular and transparent communication with the participants regarding their contribution, the use of adequate and various communication channels, shifting the workload from the participants to the coordinating team of a citizen science initiative, as well as offering feedback on the research findings to the citizen scientists, thereby disseminating the results of the program.